Promoting solid waste management and disposal through contingent valuation method: A review - Ke, Jiachao; Cai, Kaihan; Yuan, Wenyi; Li, Jinhui; Song, Qingbin (Journal of cleaner production, 2022)
As a typical declarative preference assessment method, contingent valuation method (CVM) has been widely used to improve the solid waste management and disposal. Quantifying an individual's willingness to pay (WTP) is important for promoting solid waste management and disposal. However, there is still lack of a review of the application of CVM in the field of environmental science. This study provides a systematic review of the application of CVM in solid waste management and disposal, to understand the research status and future development, and to identify the key influence factors on an individual's WTP values. Most studies have focused on five kinds of typical solid waste (construction and demolition waste, e-waste, agricultural waste, plastic waste, and municipal solid waste) and on solid waste management service. In designing the CVM questionnaire, the sample size, elicitation technology (e.g., double-bounded dichotomous choice), and survey method (e.g., face-to-face interview) were considered, to improve the CVM reliability. The results indicate that personal information (especially educational level, age, and income level), individual attitudes and perceived behavioral control were often the significant factors for residents' WTP. This study also discloses the distribution of existing studies (mainly focused on Asia) and development from the perspective of spatial and temporal distribution (diversification of research subjects), analyzes the urban-rural disparities and discusses the correlation between WTP/WTP values and regions with different economic levels. The study provides scholars with suggested questionnaire design methods and experiences, and provides policymakers with breakthrough points for improving solid waste management, through which a zero-waste city development model can be better constructed. [Display omitted] •It firstly reviews CVM application in solid waste management to identify key factors.•It provides reasonable questionnaire design to improve the CVM reliability.•Personal information (especially education, age, and income) is significant for WTP value.•Individual attitudes and PBC are significant factors for WTP value.•Research status, urban-rural disparities, and economic relationship of WTP are discussed.